Postnephrectomy rencal pedicle arteriovenous fistula - Larre Borges, Uruguay; Harretche, Martin; Mesa Figueras, Guillermo; Chiossoni, Martha (Cirugía del Uruguay, 1971)
The paper deals with a case of arteriovenous fistula of the renal pedicle, postnephrectomy, and includes a discussion of clinical aspects, pathogenesis and treatment.